Digital radiography: optimization of image quality and dose using multi-frequency software. - Precht H; Gerke O; Rosendahl K; Tingberg A; Waaler D; Precht, H; Gerke, O; Rosendahl, K; Tingberg, A; Waaler, D (Pediatric Radiology, 2012)
Background: New developments in processing of digital radiographs (DR), including multi-frequency processing (MFP), allow optimization of image quality and radiation dose. This is particularly promising in children as they are believed to be more sensitive to ionizing radiation than adults.Objective: To examine whether the use of MFP software reduces the radiation dose without compromising quality at DR of the femur in 5-year-old-equivalent anthropomorphic and technical phantoms.Materials and Methods: A total of 110 images of an anthropomorphic phantom were imaged on a DR system (Canon DR with CXDI-50 C detector and MLT[S] software) and analyzed by three pediatric radiologists using Visual Grading Analysis. In addition, 3,500 images taken of a technical contrast-detail phantom (CDRAD 2.0) provide an objective image-quality assessment.Results: Optimal image-quality was maintained at a dose reduction of 61% with MLT(S) optimized images. Even for images of diagnostic quality, MLT(S) provided a dose reduction of 88% as compared to the reference image. Software impact on image quality was found significant for dose (mAs), dynamic range dark region and frequency band.Conclusion: By optimizing image processing parameters, a significant dose reduction is possible without significant loss of image quality.